Overexpression of CDCA7 predicts poor prognosis and induces EZH2‐mediated progression of triple‐negative breast cancer. Issue 10 (19th September 2018) - Ye, Liping; Li, Fengyan; Song, Yipeng; Yu, Donglin; Xiong, Zhenchong; Li, Yue; Shi, Tianyi; Yuan, Zhongyu; Lin, Chuyong; Wu, Xianqiu; Ren, Liangliang; Li, Xinghua; et al.
Abstract : Triple‐negative breast cancer (TNBC) is the most aggressive subtype of breast cancer with high proliferative and metastatic phenotypes. CDCA7, a new member of the cell division cycle associated family of genes, is involved in embryonic development and dysregulated in various types of human cancer. However, the biological role and molecular mechanism of CDCA7 in TNBC have not been defined. Herein, we found that CDCA7 was preferentially and markedly expressed in TNBC cell lines and tissues. High expression of CDCA7 was associated with metastatic relapse status and predicted poorer disease‐free survival in patients with TNBC. We observed that CDCA7 silencing in TNBC cell lines effectively impaired cell proliferation, invasion and migration in vitro . Importantly, depletion of CDCA7 strongly reduced the tumorigenicity and distant colonization capacities of TNBC cells in vivo . Furthermore, CDCA7 increased the expression of EZH2, a marker of aggressive breast cancer that is involved in tumor progression, by enhancing the transcriptional activity of its promoter. This increase in EZH2 expression was essential for the CDCA7‐mediated effects on TNBC progression. Finally, our immunohistochemical analysis revealed that the CDCA7/EZH2 axis was clinical relevant. These findings suggest CDCA7 plays a crucial role in TNBC progression by transcriptionally upregulating EZH2 and might be a potential prognostic factor and therapeutic target in TNBC. Abstract : What's new? Cell division cycle‐associated 7 (CDCA7) protein, a c‐Myc‐interacting transcriptional regulator, is overexpressed in breast cancer, where it potentially impacts tumor development. The relevance of CDCA7 in breast cancer, however, is unknown. Here, analyses reveal marked CDCA7 upregulation in tissues from patients with highly aggressive triple‐negative breast cancer (TNBC). High CDCA7 expression was associated with metastatic relapse status and predicted poor disease‐free survival in TNBC patients. Meanwhile, in vitro silencing of CDCA7 inhibited TNBC cell proliferation and triggered TNBC cell death. Additional experiments indicate that CDCA7 transcriptionally upregulates the epigenetic modifier EZH2, thereby promoting TNBC cell aggressiveness and metastasis.